High-entropy oxide catalyst, preparation method thereof and application of high-entropy oxide catalyst in lithium-sulfur battery
Through the preparation of high-entropy oxide catalysts, the catalytic conversion problem of lithium polysulfide in lithium sulfur batteries is solved, the capacity and rate performance of the battery is improved, the application of low-cost and low-cost catalysts is realized, and the electrochemical performance and stability are enhanced. sex.
Patent Information
- Application Number
- CN202411329946.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-17
AI Technical Summary
The intermediate product lithium polysulfide produced by lithium sulfur batteries during charging and discharging leads to loss of active substances, capacity attenuation and Coulomb efficiency. The preparation of existing catalysts is complex and difficult to achieve industrial-grade production, and traditional catalysts are difficult to achieve both catalytic and adsorption effects.
Using high-entropy oxide catalysts (such as (CraCobZncMdNe) 2Ox, the metal powder mixing, ball milling and calcining are prepared by molar ratio to form a single-phase face-centered cubic high-entropy oxide, with uniform elements and submicron size. in lithium sulfur battery catalyst.
It significantly improves the specific capacity and rate performance of lithium-sulfur batteries, reduces charge and discharge polarization, realizes the application of low-cost and low-cost catalysts, enhances electrochemical performance and stability, and is suitable for practical applications.
Smart Images

Figure CN119318966A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and in particular to a high entropy oxide catalyst, a preparation method thereof, and application thereof in a lithium-sulfur battery. Background Art
[0002] Lithium-sulfur batteries have high theoretical specific capacity and specific energy density, and their active sulfur raw materials are abundant, low-cost and environmentally friendly, making them one of the important next-generation secondary battery systems that can be practically applied. However, the intermediate product lithium polysulfide produced during the charge and discharge process of liquid lithium-sulfur batteries will inevitably form a shuttle effect, leading to the loss of active materials, capacity decay and reduced coulombic efficiency. These problems have seriously hindered the application of lithium-sulfur batteries.
[0003] In recent years, research on catalytic materials for lithium-sulfur batteries can adsorb lithium polysulfide and catalyze its conversion, alleviate the shuttle effect, and improve reaction kinetics. However, faced with the complex multi-step reaction of polysulfides. The effects produced by traditional transition metal catalysts are difficult to meet application requirements. The preparation of existing catalysts is often complicated, and few have the ability to produce at an industrial level. In addition, most catalysts are nanoscale particles, which have more stringent requirements for preparation, preservation, and water and oxygen. At the same time, the design of most catalysts currently focuses on one aspect, such as catalytic effect or adsorption effect, and there are few designs that cover multiple directions. High entropy oxides can form a synergistic effect through the complex interactions of their different elements, surpassing the characteristics of a single element, and can provide multiple catalytic active sites, showing great research potential in lithium-sulfur batteries.
[0004] There is little research on the application of existing high-entropy oxide catalysts in lithium-sulfur batteries. Designing a high-entropy oxide catalyst with strong catalytic adsorption effect prepared through a simple process that can be industrialized is crucial for the application and development of lithium-sulfur batteries. Summary of the invention
[0005] In view of the above analysis, the present invention aims to provide a high entropy oxide catalyst and a preparation method thereof and its application in a lithium-sulfur battery, so as to solve at least one of the problems that the existing catalyst has low catalytic activity on the positive electrode of the lithium-sulfur battery, the prepared lithium-sulfur battery has poor cycle performance, poor rate performance, poor capacity utilization, high production cost, etc.
[0006] In a first aspect, the present invention provides a high entropy oxide catalyst, the general formula of the catalyst is (Cr a Co b Zn c M d N e ) 2 O x, wherein 0.15≤a≤0.25, 0.15≤b≤0.25, 0.15≤c≤0.25, 0.15≤d≤0.25, 0.15≤e≤0.25, and a+b+c+d+e=1, 0.8≤x≤1.5, M and N are any one of Mn, Fe, and Cu respectively, and M and N are different elements.
[0007] Furthermore, the high entropy oxide catalyst is a single-phase face-centered cubic high entropy oxide with uniform element distribution and a particle size of submicron level.
[0008] In a second aspect, the present invention provides a method for preparing the high entropy oxide catalyst, comprising the following steps:
[0009] (1) weighing the metal powders according to the molar ratio, mixing to obtain a mixed metal powder, and ball milling to obtain a powder;
[0010] (2) calcining the powder to obtain the high entropy oxide catalyst.
[0011] Furthermore, in step (1), an organic solvent is added during the ball milling process, and the mass of the organic solvent is 2-4% of the mass of the mixed metal powder. Preferably, the organic solvent is toluene and / or anhydrous ethanol.
[0012] Furthermore, in step (1), the ball milling speed is 250-350 rpm, and the ball milling time is 25-40 h.
[0013] Furthermore, the ball milling is performed at least 60 times.
[0014] Furthermore, the single ball milling time is 30 to 40 minutes, the interval between two adjacent ball millings is 3 to 5 minutes, and the powder is naturally cooled in the tank for 12 to 36 hours after the ball milling.
[0015] Furthermore, in step (2), the calcination temperature is 400-600°C, the calcination time is 1-3h, and the heating rate is 5-10°C / min.
[0016] In a third aspect, the present invention provides a lithium-sulfur battery sulfur positive electrode sheet, comprising the above-mentioned high entropy oxide catalyst.
[0017] In a fourth aspect, the present invention provides a lithium-sulfur battery, comprising the positive electrode sheet.
[0018] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0019] (1) Compared with other high entropy oxides using metals such as Al, Mg, Ti or rare metals, the present invention uses abundant resources such as Cr, Co, Zn, Mn, Fe, Cu, etc. to synthesize high entropy oxides, while ensuring good catalytic and adsorption performance, and controlling the production cost, so that it can be used as a low-cost catalyst for the catalytic conversion of polysulfides in lithium-sulfur batteries; when the high entropy oxide catalyst of the present invention is used as a lithium-sulfur battery catalyst, the specific capacity and rate performance of the lithium-sulfur battery are significantly improved, and its charge and discharge polarization is reduced, and at the same time, the practical application of Ah-level soft packs is realized;
[0020] (2) The high entropy oxides described in the present invention rationally utilize the advantage of "high entropy" - synergy, that is, through the complex interaction of different elements, a synergistic effect is formed, which can often surpass the characteristics of a single element and ultimately obtain an overall performance that exceeds expectations. The active elements Cr, Co, Zn, and Mn can all provide strong catalytic and adsorption properties, and the highly conductive elements Fe and Cu promote rapid electron conduction. In the multi-stage reaction lithium-sulfur battery, the advantages of different elements are perfectly integrated, improving the electrochemical performance and stability;
[0021] (3) Compared with traditional single alloys or binary and ternary alloys, the high entropy oxide catalyst of the present invention is a single-phase face-centered cubic high entropy oxide, which has the characteristics of uniform element distribution and submicron-level 0.1μm-1.0um small particle size, which is conducive to exerting stronger catalytic and adsorption effects on multiple reactions. It can be used as a lithium-sulfur battery positive electrode catalyst by adding a small amount to provide good gram capacity, cycle stability and rate performance, further improving its energy density.
[0022] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.
[0024] Figure 1 The XRD pattern of the catalyst prepared in Example 1 of the present invention;
[0025] Figure 2 TEM lattice spacing image of the catalyst prepared in Example 1 of the present invention;
[0026] Figure 3The SEM and element distribution diagram of the catalyst prepared in Example 1 of the present invention;
[0027] Figure 4 The rate performance diagram of the battery prepared by the positive electrode of the lithium-sulfur battery prepared by the test sample and the control sample in Test Example 3 of the present invention;
[0028] Figure 5 It is a lithium sulfide deposition curve diagram of the test sample and the comparative sample in Test Example 4 of the present invention;
[0029] Figure 6 This is a graph showing the change of the adsorption of lithium polysulfide over time for the test sample of Test Example 5 and the control sample 1-2 of the present invention;
[0030] Figure 7 CV curves of the test sample and the control sample in Test Example 6 of the present invention. DETAILED DESCRIPTION
[0031] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.
[0032] A specific embodiment of the present invention discloses a high entropy oxide catalyst (abbreviated as HEO), the general formula of the catalyst is (Cr a Co b Zn c M d N e ) 2 O x , wherein 0.15≤a≤0.25, 0.15≤b≤0.25, 0.15≤c≤0.25, 0.15≤d≤0.25, 0.15≤e≤0.25, and a+b+c+d+e=1, 0.8≤x≤1.5, M and N are any one of Mn, Fe, and Cu respectively, and M and N are different elements.
[0033] For example, a is 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, b is 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, and c is 0.15, 0.16, 0. 17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, d is 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, and x is 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5.
[0034] Here, x represents the degree of oxidation. If the degree of oxidation is too low or too high, it will affect the formation of the high entropy oxide structure, and thus affect the electrical performance of the battery.
[0035] Compared with other high entropy oxides that use metals such as Al, Mg, Ti or rare metals, the present invention uses abundant resources such as Cr, Co, Zn, Mn, Fe, Cu, etc. to synthesize high entropy oxides, while ensuring good catalytic and adsorption properties, and controlling production costs, so that it can be used as a low-cost catalyst for the catalytic conversion of polysulfides in lithium-sulfur batteries; when the high entropy oxide catalyst of the present invention is used as a lithium-sulfur battery catalyst, the specific capacity and rate performance of the lithium-sulfur battery are significantly improved, and its charge and discharge polarization is reduced, and the practical application of Ah-level soft packs is realized.
[0036] The high entropy oxide developed by the present invention rationally utilizes the advantage of "high entropy" - synergy, that is, through the complex interaction of different elements, a synergistic effect is formed, which can often surpass the characteristics of a single element and ultimately obtain an overall performance that exceeds expectations. The active elements Cr, Co, Zn, and Mn can all provide strong catalysis and adsorption, and the highly conductive elements Fe and Cu promote rapid electron conduction. The advantages of different elements are perfectly integrated in the multi-stage reaction lithium-sulfur battery, which improves the electrochemical performance and stability.
[0037] The high entropy oxide catalyst of the present invention has good stability and low sensitivity to water and oxygen. It does not require high battery preparation technology. If higher capacity and cycle requirements are required for the battery, carbon coating, nano-sizing and other methods can be used to improve performance, and it has good improvement adaptability.
[0038] Preferably, in order to ensure that the catalyst has a good catalytic effect on multiple reaction processes, the molar ratios of the elements in the catalyst are the same or similar. When equal atoms or similar atoms are occupied, there will be the largest configurational entropy and the highest cation disorder. If a single element deviates too much, it may lead to the inability to form a corresponding crystal structure and a corresponding high entropy state. A large configurational entropy is believed to enhance the effects of surface chemistry and synergy. Therefore, it is further preferred that 0.19≤a≤0.21, 0.19≤b≤0.21, 0.19≤c≤0.21, 0.19≤d≤0.21, 0.19≤e≤0.21; more preferably, a=b=c=d=e=0.2.
[0039] It should be noted that Fe and Cu have smaller atomic radii and are closer to Co and Zn in electronegativity, which makes it easier to form doping. At the same time, they all have the ability to catalyze redox reactions. Considering the price cost of metals, catalysts, and the doping distortion effect, the five elements of the catalyst of the present invention are preferably Cr, Co, Zn, Fe, and Cu.
[0040] In a specific embodiment, the high entropy oxide catalyst is a single-phase face-centered cubic high entropy oxide with uniform element distribution and a particle size of submicron level.
[0041] Preferably, the submicron level is 0.1 μm-1.0 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm.
[0042] Compared with traditional single alloys or binary and ternary alloys, the high entropy oxide catalyst of the present invention is a single-phase face-centered cubic high entropy oxide, which has the characteristics of uniform element distribution and submicron-level 0.1μm-1.0um small particle size, which is conducive to exerting stronger catalytic and adsorption effects on multiple reactions. It can be used as a positive electrode catalyst for lithium-sulfur batteries with a small amount of addition (about 5% of the total active material) to provide good gram capacity, cycle stability and rate performance, and further improve its energy density. The soft pack energy density reaches 300wh kg -1 , reach commercial level and solve a series of problems faced by traditional lithium-sulfur batteries.
[0043] The high entropy oxide material described in the present invention has good stability and low sensitivity to water and oxygen. It does not require high battery preparation technology. If higher capacity and cycle requirements are required for the battery, carbon coating, nano-sizing and other methods can be used to improve performance, and it has good improvement adaptability.
[0044] In a second aspect, the present invention provides a method for preparing a high entropy oxide catalyst, comprising the following steps:
[0045] (1) weighing the metal powders according to the molar ratio, mixing to obtain a mixed metal powder, and ball milling to obtain a powder;
[0046] (2) calcining the powder to obtain the high entropy oxide catalyst.
[0047] In a specific embodiment, in step (1), ball milling is performed in a ball milling jar, and the ball milling jar is a zirconia ball milling jar.
[0048] Preferably, zirconium beads are added to the ball mill at a ball-to-material ratio of 20:1, which can ensure that there is sufficient total energy during ball milling and provide the necessary conditions for the formation of high entropy oxides. The sizes of zirconium beads are 15mm, 10mm and 1mm, and the quantity ratio is 5:4:1 (1mm zirconium beads can be added as appropriate for balance). The above ratio can ensure that various elements can be mixed and reacted more fully, provide sufficient collision shear force, and reduce the powder particle size.
[0049] In a specific embodiment, an organic solvent is further added to the ball mill, and the mass of the organic solvent is 2-4% of the mass of the mixed metal powder, for example, 2%, 2.5%, 3.0%, 3.5%, 4%. Preferably, the organic solvent is toluene and / or anhydrous ethanol. The organic solvent is used as a ball milling process control agent to prevent cold welding. If the ratio is lower than 2%, the cold welding inhibition effect is not obvious. If the ratio is higher than 4%, too much liquid is not conducive to uniform ball milling. The zirconium tank is evacuated and then flushed with argon or other inert gas to prevent oxidation in the subsequent ball milling process.
[0050] In a specific embodiment, in step (1), the ball milling speed is 250-350 rpm, for example, 250 rpm, 260 rpm, 270 rpm, 280 rpm, 290 rpm, 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm, 350 rpm, and the ball milling time is 25-40 h, for example, 25 h, 26 h, 27 h, 28 h, 29 h, 30 h, 31 h, 32 h, 33 h, 34 h, 35 h, 36 h, 37 h, 38 h, 39 h, 40 h.
[0051] In the present invention, ball milling allows the elements to be doped with each other to form an alloy solid solution.
[0052] Preferably, the ball milling is performed at least 60 times.
[0053] More preferably, the single ball milling time is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min, the interval between two adjacent ball millings is 3 to 5 min, for example, 3 min, 3.5 min, 4 min, 4.5 min, 5 min, and the powder is naturally cooled in the tank for 12 to 36 h after the ball milling, for example, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, 30 h, 32 h, 34 h, 36 h.
[0054] More preferably, the rotation speed is 300 rpm, the single ball milling time is 30 min, the interval is 5 min, and the ball milling time is 30 h.
[0055] It should be noted that the ball milling speed should not be too high and the time should not be too long, otherwise it is easy to cause the temperature to be too high and cold welding to occur. The speed should not be too low and the time should not be too short, otherwise the insufficient ball milling energy will easily lead to incomplete reaction, and some raw materials will not react completely after the reaction is completed. The speed and ball milling time of the present invention can well provide sufficient energy for the reaction, so that the reaction can be fully carried out.
[0056] In a specific embodiment, in step (2), the calcination temperature is 400-600°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C, 600°C; the calcination time is 1-3h, for example, 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2.0h, 2.2h, 2.4h, 2.6h, 2.8h, 3h; and the heating rate is 5-10°C / min, for example, 5°C / min, 5.5°C / min, 6°C / min, 6.5°C / min, 7°C / min, 7.5°C / min, 8°C / min, 8.5°C / min, 9°C / min, 9.5°C / min, 10°C / min.
[0057] It should be noted that the calcination of the present invention is carried out in the air, the purpose is to oxidize the metal alloy to form a high entropy oxide, the calcination temperature is lower than 400 ° C, the oxidation reaction is slow and the reaction is not sufficient, the calcination temperature is higher than 600 ° C, the structure of the oxidized product changes, and the target product cannot be formed at too high or too low a temperature. In addition, if the heating rate is too low, the high-temperature calcination time is increased, and the degree of oxidation is not controlled, and if the heating rate is too high, the material is heated unevenly locally, and the high entropy oxide has local structural differences.
[0058] The present invention adopts a simple ball milling and high-temperature calcination process, which is easy to synthesize on a large scale, consumes less energy, has high yield, high purity and low cost. Compared with other high-entropy oxides that require hydrothermal method and rapid temperature rise calcination preparation, the production cost and safety are improved.
[0059] Another specific embodiment of the present invention discloses a sulfur positive electrode sheet for a lithium-sulfur battery, comprising the high entropy oxide catalyst described above.
[0060] Specifically, the high entropy oxide catalyst accounts for 3-8% of the total mass of the active material, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%.
[0061] It should be noted that when the amount of the high entropy oxide catalyst added is less than 3%, the catalyst active sites are too few, the catalytic effect is reduced, and the catalyst resistivity is larger than the carbon material in the positive electrode of the lithium-sulfur battery. If the added content is higher than 8%, the resistivity of the electrode will increase and affect the battery performance.
[0062] Another specific embodiment of the present invention discloses a lithium-sulfur battery, comprising the above-mentioned positive electrode sheet.
[0063] The technical solution of the present invention is further explained below in conjunction with specific embodiments.
[0064] Example 1
[0065] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.2 Co 0.2 Zn 0.2 Fe 0.2 Cu 0.2 ) 2 O, the preparation method of the catalyst of this embodiment is as follows:
[0066] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and copper powder (Macklin, 99.9%) were weighed in a specific molar ratio (1:1:1:1:1), and added into a zirconia ball mill, wherein the ball-to-material ratio of zirconia beads to powder material was 20:1, and the sizes of the zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added into the ball mill, and the mass of the toluene was 2% of the mass of the mixed metal powder; the zirconium can was placed in a glove box, filled with inert gas (Ar gas), and the glove box was guaranteed to be free of water and oxygen (all <0.01 ppm), and then sealed;
[0067] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 12 h to obtain a metal powder mixture;
[0068] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 5° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0069] The XRD pattern of the catalyst prepared in this example is as follows Figure 1 , combined with Figure 2 The TEM lattice spacing diagram shows that a cubic structure solid solution was prepared, and the metal elements are not simply physically mixed. The SEM and EDS of the sulfur-carbon electrode with the high-entropy oxide catalyst added are as follows: Figure 3 As shown, the high entropy oxide catalyst is uniformly attached with sulfur and carbon materials, and the particle size is submicron level (0.1μm-1.0um). Figure 3 The EDS image in the middle shows that the elements in the high entropy oxide catalyst particles are evenly distributed.
[0070] Example 2
[0071] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.2 Co 0.2 Zn 0.2 Mn 0.2 Cu 0.2 ) 2 O 1.5 , the preparation method of the catalyst of this embodiment is as follows:
[0072] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), manganese powder (Macklin, 99%), and copper powder (Macklin, 99.9%) are weighed in a specific molar ratio (1:1:1:1:1) and added to a zirconium oxide ball mill. The ball-to-material ratio of zirconium oxide beads to powder materials is 20:1. The sizes of zirconium beads are 15 mm, 10 mm, and 1 mm, and the quantity ratio is 5:4:1. Toluene is also added to the ball mill. The mass of the toluene is 3% of the mass of the mixed metal powder. The zirconium can is placed in a glove box and filled with inert gas (Ar gas). The glove box is guaranteed to be free of water and oxygen (all <0.01 ppm), and then sealed;
[0073] (2) taking out the ball milling jar, ball milling at a speed of 350 rpm / min for 35 min and then resting for 3 min, the total ball milling time is 25 h. After the ball milling, the powder is naturally cooled in the jar for 24 h to obtain a metal powder mixture;
[0074] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 400° C., the heating rate was 7.5° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0075] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0076] Example 3
[0077] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.2 Co 0.2 Zn 0.2 Mn 0.2 Fe 0.2 ) 2 O, the preparation method of the catalyst of this embodiment is as follows:
[0078] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and manganese powder (Macklin, 99.9%) were weighed in a specific molar ratio (1:1:1:1:1), and added to a zirconia ball mill, wherein the ratio of zirconia beads to powder material was 20:1, and the sizes of the zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added to the ball mill, and the mass of the toluene was 4% of the mass of the mixed metal powder; the zirconium can was placed in a glove box, filled with inert gas (Ar gas), and the glove box was guaranteed to be free of water and oxygen (all <0.01 ppm), and then sealed;
[0079] (2) taking out the ball milling jar, ball milling at a speed of 250 rpm / min for 40 min and then resting for 4 min, the total ball milling time is 40 h. After the ball milling, the powder is naturally cooled in the jar for 36 h to obtain a metal powder mixture;
[0080] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 600° C., the heating rate was 10° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0081] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0082] Example 4
[0083] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.2Co 0.2 Zn 0.2 Fe 0.2 Cu 0.2 ) 2 O 1.5 , the preparation method is as follows:
[0084] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and copper powder (Macklin, 99.9%) were weighed in a specific molar ratio (1:1:1:1:1), and added to a zirconia ball mill, wherein the ball-to-material ratio of zirconia beads to powder material was 20:1, and the sizes of the zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added to the ball mill, and the mass of the toluene was 2.5% of the mass of the mixed metal powder; the zirconium can was placed in a glove box, filled with inert gas (Ar gas), and the glove box was guaranteed to be free of water and oxygen (all <0.01 ppm), and then sealed;
[0085] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 18 h to obtain a metal powder mixture;
[0086] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 8° C. / min, and the calcination time was 3 h to obtain the catalyst.
[0087] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0088] Example 5
[0089] A high entropy oxide catalyst of this embodiment has a molecular formula of (Cr 0.2 Co 0.2 Zn 0.2 Fe 0.2 Cu 0.2 ) 2 O 0.8 , the preparation method is as follows:
[0090] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and copper powder (Macklin, 99.9%) were weighed in a specific molar ratio (1:1:1:1:1), and added into a zirconia ball mill, wherein the ball-to-material ratio of zirconia beads to powder material was 20:1, and the sizes of the zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added into the ball mill, and the mass of the toluene was 3.5% of the mass of the mixed metal powder; the zirconium can was placed in a glove box, filled with inert gas (Ar gas), and the glove box was guaranteed to be free of water and oxygen (all <0.01 ppm), and then sealed;
[0091] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 30 h to obtain a metal powder mixture;
[0092] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 5° C. / min, and the calcination time was 1 h to obtain the catalyst.
[0093] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0094] Example 6
[0095] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.19 Co 0.21 Zn 0.2 Mn 0.19 Cu 0.21 ) 2 O, the preparation method is as follows:
[0096] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), manganese powder (Macklin, 99%), and copper powder (Macklin, 99.9%) were weighed in a specific molar ratio (19:21:20:19:21) and added to a zirconia ball mill. The ball-to-material ratio of zirconia beads to powder material was 20:1. The sizes of zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added to the ball mill. The mass of the toluene was 2% of the mass of the mixed metal powder. The zirconium can was placed in a glove box and filled with inert gas (Ar gas). The glove box was ensured to be free of water and oxygen (all <0.01 ppm), and then sealed.
[0097] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 36 h to obtain a metal powder mixture;
[0098] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 7° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0099] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0100] Example 7
[0101] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.21 Co 0.19 Zn 0.21 Fe 0.19 Cu 0.2 ) 2 O, the preparation method is as follows:
[0102] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and copper powder (Macklin, 99.9%) were weighed in a specific molar ratio (21:19:21:19:20) and added to a zirconia ball mill, wherein the ratio of zirconia beads to powder material was 20:1, and the sizes of the zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added to the ball mill, and the mass of the toluene was 3.5% of the mass of the mixed metal powder; the zirconium can was placed in a glove box, filled with inert gas (Ar gas), and the glove box was guaranteed to be free of water and oxygen (all <0.01 ppm), and then sealed;
[0103] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 30 h to obtain a metal powder mixture;
[0104] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 9° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0105] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0106] Example 8
[0107] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.15 Co 0.15 Zn 0.2 Fe 0.25 Cu 0.25 ) 2 O, the preparation method is as follows:
[0108] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and copper powder (Macklin, 99.9%) were weighed in a specific molar ratio (3:3:4:5:5) and added to a zirconia ball mill. The ball-to-material ratio of zirconia beads to powder material was 20:1. The sizes of zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added to the ball mill. The mass of the toluene was 4.5% of the mass of the mixed metal powder. The zirconium can was placed in a glove box and filled with inert gas (Ar gas). The glove box was ensured to be free of water and oxygen (all <0.01 ppm), and then sealed.
[0109] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 28 h to obtain a metal powder mixture;
[0110] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 7° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0111] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0112] Example 9
[0113] A high entropy oxide catalyst of this embodiment has a molecular formula of (Cr 0.25 Co 0.25 Zn 0.2 Mn 0.15 Cu 0.15 ) 2 O, the preparation method is as follows:
[0114] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), manganese powder (Macklin, 99%), and copper powder (Macklin, 99.9%) were weighed in a specific molar ratio (5:5:4:3:3) and added to a zirconia ball mill. The ball-to-material ratio of zirconia beads to powder material was 20:1. The sizes of zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added to the ball mill. The mass of the toluene was 5.5% of the mass of the mixed metal powder. The zirconium can was placed in a glove box and filled with inert gas (Ar gas). The glove box was ensured to be free of water and oxygen (all <0.01 ppm), and then sealed.
[0115] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 32 h to obtain a metal powder mixture;
[0116] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 6° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0117] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0118] Example 10
[0119] A high entropy oxide catalyst of this embodiment has the general formula of (Cr 0.2 Co 0.25 Zn 0.15 Fe 0.25 Mn 0.15 ) 2 O, the preparation method is as follows:
[0120] (1) Chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and manganese powder (Macklin, 99.9%) were weighed in a specific molar ratio (4:5:3:5:3) and added to a zirconia ball mill, wherein the ratio of zirconia beads to powder material was 20:1, and the sizes of the zirconium beads were 15 mm, 10 mm, and 1 mm, and the quantity ratio was 5:4:1. Toluene was also added to the ball mill, and the mass of the toluene was 2.5% of the mass of the mixed metal powder; the zirconium can was placed in a glove box, filled with inert gas (Ar gas), and the glove box was guaranteed to be free of water and oxygen (all <0.01 ppm), and then sealed;
[0121] (2) taking out the ball milling jar, ball milling at a speed of 300 rpm / min for 30 min, and then resting for 5 min, the total ball milling time is 30 h. After the ball milling, the powder is naturally cooled in the jar for 40 h to obtain a metal powder mixture;
[0122] (3) The powder obtained after ball milling was calcined under air, the calcination temperature was 500° C., the heating rate was 7° C. / min, and the calcination time was 2 h to obtain the catalyst.
[0123] The catalyst prepared in this example was tested in the same manner as in Example 1, and the results were basically consistent. Due to limited space, they are not listed one by one.
[0124] Comparative Example 1
[0125] The chemical formula of the catalyst in this comparative example is (Cr 0.1 Co 0.1 Zn 0.3 Fe 0.4 Cu 0.2 ) 2 O 2 In the preparation method, chromium powder (Macklin, 99.9%), cobalt powder (Macklin, 99.9%), zinc powder (Shanghai Hushi, 99.9%), iron powder (Macklin, 99%), and copper powder (Macklin, 99.9%) are weighed according to a specific molar ratio (1:1:3:4:2), and the rest is the same as Example 10.
[0126] Comparative Example 2
[0127] The chemical formula of the catalyst in this comparative example is (Cr 0.2 Co 0.2 Zn 0.2 ) 2 O. In the preparation method, chromium powder (Macklin, 99.9%), cobalt powder (Shanghai Hushi, 99.9%), and zinc powder (Macklin, 99.9%) are weighed according to a specific molar ratio (1:1:1), and the rest is the same as Example 1.
[0128] Comparative Example 3
[0129] The catalyst of this comparative example is commercially available cobalt powder with a purity of 99.9%.
[0130] Comparative Example 4
[0131] The chemical formula of the catalyst in this comparative example is the same as that in Example 1, except that in step (1), the total ball milling time is 20 h, and is recorded as the catalyst of comparative example 4.
[0132] Comparative Example 5
[0133] The chemical formula of the catalyst of this comparative example is the same as that of Example 1, except that in step (2), the calcination temperature is 350° C., and is recorded as the catalyst of Comparative Example 5.
[0134] Test Example 1: Button Battery Charge and Discharge Cycle Test
[0135] (1) The catalysts of Examples 1-10 and Comparative Examples 1-5 were respectively mixed with 65% sulfur and 30% carbon nanotubes at a mass ratio of 5% by mass by ball milling, and then kept at 155° C. under semi-vacuum for 9 hours to obtain the active material of the electrode sheet, and then mixed with the active material: binder = 9:1, and then coated, dried and cut to obtain the positive electrode sheet, which were recorded as test samples 1-10 and control samples 1-5 respectively;
[0136] (2) The catalyst of Example 1 was mixed with 67% sulfur and 30% carbon nanotubes at a mass ratio by ball milling at 3% by mass, and then kept at 155° C. under semi-vacuum for 9 hours to obtain an active material for the electrode sheet. Subsequently, a slurry was mixed at a ratio of active material to binder of 9:1, and the positive electrode sheets were obtained after coating, drying and cutting, which were respectively recorded as test samples 11;
[0137] (3) The catalyst of Example 1 was mixed with 62% sulfur and 30% carbon nanotubes in a ball mill at a mass ratio of 8%, and then kept at 155° C. under semi-vacuum for 9 hours to obtain an active material for the electrode. Then, a slurry was mixed at a ratio of active material to binder of 9:1, and the positive electrode was obtained after coating, drying and cutting, which were respectively recorded as test samples 12;
[0138] (4) The catalyst of Example 1 was mixed with 60% sulfur and 30% carbon nanotubes in a ball mill at a mass ratio of 10%, and then kept at 155° C. under semi-vacuum for 9 hours to obtain an active material for the electrode. Subsequently, a slurry was mixed at a ratio of active material to binder of 9:1, and the positive electrode was obtained after coating, drying and cutting, which were respectively recorded as control sample 6;
[0139] (5) The catalyst of Example 1 was mixed with 68% sulfur and 30% carbon nanotubes in a ball mill at a mass ratio of 2%, and then kept at 155° C. under semi-vacuum for 9 hours to obtain an active material for the electrode. Subsequently, a slurry was mixed at a ratio of active material to binder of 9:1, and the positive electrode was obtained after coating, drying and cutting, which were respectively recorded as control sample 7;
[0140] (6) A lithium-sulfur battery positive electrode without any catalyst was used as a blank test. Specifically, the positive electrode was prepared by mixing 70% sulfur and 30% carbon nanotubes by weight in a ball mill, and then heat-preserving at 155°C under semi-vacuum for 9 hours to obtain the active material of the electrode. Subsequently, a slurry was mixed according to the ratio of active material to binder = 9:1, and the positive electrode was obtained after coating, drying and cutting, which was recorded as control sample 8.
[0141] (7) The positive electrodes of the lithium-sulfur batteries of the test samples 1-12 and the control samples 1-8 were assembled into CR2025 button batteries with lithium sheets and PP separators, and 70uL 1M LiTFSIDOL / DME+2%LiNO 3 .
[0142] The assembled battery was subjected to a cycle performance test. After the battery was left to stand for 5 hours, it was discharged and charged at a rate of 0.1C for two cycles, and then discharged and charged at a rate of 0.5C for 300 cycles. The first cycle efficiency, gram capacity, and capacity retention were tested. The capacity and efficiency of the test samples 1-10 and the control samples 1-4 at a rate of 0.5C for 300 cycles are shown in Table 1.
[0143] Table 1
[0144]
[0145]
[0146]
[0147]
[0148]
[0149] According to the comparison between the control samples 1-8 and the test samples 1-12, it can be seen that the catalysts obtained by not being within the scope specified by the present invention in terms of the number of element types, the ratio of elements, and the degree of oxidation, or without adding a catalyst, the batteries prepared have lower 0.1C first cycle gram capacity and lower retention rate after 300 cycles at 0.5C, and the charge and discharge platform pressure difference is larger.
[0150] According to test samples 1, 4 and 5, the values of x in the catalyst chemical formula are different, that is, the degree of oxidation is different, and the performance of the prepared batteries is different. When x=1, the electrical performance of the battery is optimal.
[0151] According to test samples 1, 7, 8 and 2, 6, 9, it can be seen that when 0.19≤a≤0.21, 0.19≤b≤0.21, 0.19≤c≤0.21, 0.19≤d≤0.21, and 0.19≤e≤0.21 in the catalyst chemical formula, the prepared battery performance is better, and when a=b=c=d=c, the battery performance is best.
[0152] According to test sample 1 and control samples 4-5, the catalyst prepared without the ball milling time or calcination temperature specified in the present invention has poor electrochemical performance when added to the positive electrode to prepare the battery, and cannot achieve the experimental effect of the catalyst of the present invention.
[0153] According to test samples 1, 11-12 and control samples 6-7, the performance of the prepared batteries is different when the catalyst addition amount is different. When the addition amount is 3%-8%, the electrical performance of the battery is better. When the addition amount is lower than 3% or higher than 8%, the battery performance is relatively reduced.
[0154] Test Example 2: Ah-class soft-pack battery charge and discharge cycle test
[0155] (1) The catalyst of Example 1 was mixed with 65% sulfur and 30% carbon nanotubes by mass in a ball mill at a mass ratio of 5%, and then kept warm at 155°C under semi-vacuum for 9 hours to obtain an active material for the electrode sheet, and then mixed with active material: binder = 9:1, and then coated, dried and cut to obtain a positive electrode sheet, which was recorded as a test sample; a lithium-sulfur battery positive electrode sheet without any catalyst was used as a blank test. Specifically, the positive electrode sheet was mixed with 70% sulfur and 30% carbon nanotubes by mass in a ball mill, and then kept warm at 155°C under semi-vacuum for 9 hours to obtain an active material for the electrode sheet, and then mixed with active material: binder = 9:1, and then coated, dried and cut to obtain a positive electrode sheet, which was recorded as a control sample.
[0156] (2) The positive electrodes of the test sample and the control sample lithium-sulfur battery were cut into 6.5 cm × 4.5 cm positive electrode sheets, and prepared into 4-layer soft-pack batteries with lithium foil and PP separator. 1M LiTFSIDOL / DME + 2% LiNO was added to the electrolyte. 3 .
[0157] The assembled soft-pack battery was subjected to a charge and discharge test. After the battery was left to rest for 24 hours, it was discharged and charged at a rate of 0.05C for 50 cycles. The specific data is shown in Table 2.
[0158] Table 2
[0159]
[0160] According to the test sample and control sample soft-pack batteries, adding the catalyst of Example 1 to the positive electrode can make the soft-pack battery have a greater capacity. Under the condition of high sulfur surface loading and low E / S, the capacity of the four-layer soft-pack battery reaches 1.26Ah, the energy density is greatly improved, and the cycle life is increased.
[0161] Test Example 3 Rate Performance Test
[0162] (1) The catalyst of Example 1 was mixed with 65% sulfur and 30% carbon nanotubes by mass in a ball mill at a mass ratio of 5%, and then kept warm at 155°C under semi-vacuum for 9 hours to obtain an active material for the electrode sheet, and then mixed with active material: binder = 9:1, and then coated, dried and cut to obtain a positive electrode sheet, which was recorded as a test sample; a lithium-sulfur battery positive electrode sheet without any catalyst was used as a blank test. Specifically, the positive electrode sheet was mixed with 70% sulfur and 30% carbon nanotubes by mass in a ball mill, and then kept warm at 155°C under semi-vacuum for 9 hours to obtain an active material for the electrode sheet, and then mixed with active material: binder = 9:1, and then coated, dried and cut to obtain a positive electrode sheet, which was recorded as a control sample.
[0163] (2) The positive electrodes of the test sample and the control sample lithium-sulfur battery were assembled into CR2025 button batteries with lithium sheets and PP separators, and 70uL 1M LiTFSIDOL / DME+2%LiNO 3 , the assembled battery was subjected to a rate performance test. After the battery was left to stand for 5 hours, it was discharged and charged at 0.1C, 0.3C, 0.5C, 1C, 1.5C, 2C, and 3C for 5 cycles, and then discharged and charged at 0.5C for 10 cycles to test the battery capacity at different rates. The results are as follows Figure 4 shown.
[0164] from Figure 4 It can be seen that the addition of the catalyst of Example 1 has better rate performance than the blank control sample without adding the catalyst, and has a higher gram capacity at a high rate.
[0165] Test Example 4 Lithium sulfide precipitation test
[0166] (1) The catalyst of Example 1 was mixed with carbon nanotubes (CNT) in equal proportions and coated on a carbon-coated aluminum foil to prepare a catalyst having an active material content of 0.5 mg / cm 2 The test sample pole piece was coated with carbon nanotubes and loaded on carbon-coated aluminum foil to prepare an active material content of 0.5 mg / cm 2 Comparison sample pole piece.
[0167] (2) The test sample and control sample electrodes were mixed with 0.2 mol L – 1 Li 2 S 8 TEGDME electrolyte, lithium foil negative electrode, and PP separator were assembled into CR2025 button batteries and marked as test samples and comparison samples.
[0168] The assembled battery was subjected to a lithium sulfide precipitation test. The battery was discharged at a constant current of 0.112 mA to 2.06 V, and then the potential was maintained at 2.05 V until the current dropped below 10-5 A. During the constant voltage discharge stage, the current was recorded over time, and a lithium sulfide deposition curve was drawn. The lithium sulfide deposition amounts of the two positive electrodes were obtained by fitting. The results are shown in the figure. Figure 5 shown.
[0169] from Figure 5 It can be seen that the comparison sample is compared with the test sample: the battery with the catalyst of Example 1 has a larger current peak value and a larger fitting area during the voltage discharge process, that is, the lithium sulfide deposition speed is faster and the deposition amount is larger, indicating that the high entropy oxide can greatly catalyze the formation of lithium polysulfide into Li 2 S.
[0170] Test Example 5 Polysulfide Adsorption Test
[0171] (1) Li 2 S 6 For polysulfide representatives, adsorption experiments were conducted by subliming sulfur and lithium sulfide (Li 2 S) was mixed in 1,3-dioxolane / 1,2-dimethoxyethane (DOL / DME, volume ratio 1:1) at a molar ratio of 5:1 to prepare iLi 2 S 6 The solution was then stirred at 60 °C overnight in an argon-filled glove box to obtain brown-red Li 2 S 6 Then, Li 2 S 6 The solution was diluted to a concentration of 5 mmol / L -1 .
[0172] (2) 50 mg of sample (catalyst Cr of Example 1) was added 0.2 Co 0.2 Zn 0.2 Fe 0.2 Cu 0.2 ) 2 O, and control sample CNT were added to 10mL Li 2 S 6 The solution was marked as test sample and control sample 1, and 10 mL Li was taken without adding any sample. 2 S 6 The solution was used as a blank control and marked as control sample 2. A digital camera was used to record the changes in the adsorption of lithium polysulfide over time. The results are shown in Figure 6 .
[0173] according to Figure 6It can be seen that the test sample is compared with the control samples 1 and 2. As the standing time increases, the test sample solution gradually becomes clear, and the polysulfide is gradually adsorbed. 0.2 Co 0.2 Zn 0.2 Fe 0.2 Cu 0.2 ) 2 O has a strong adsorption effect on polysulfides. When added to the lithium-sulfur cathode, it is beneficial to inhibit the shuttling of polysulfides and enhance the cycle stability of the battery.
[0174] Test Example 6 Cyclic Voltammetry Test
[0175] (1) The catalyst of Example 1 was mixed with 65% sulfur and 30% carbon nanotubes by mass in a ball mill at a mass ratio of 5%, and then kept warm at 155°C under semi-vacuum for 9 hours to obtain an active material for the electrode sheet, and then mixed with active material: binder = 9:1, and then coated, dried and cut to obtain a positive electrode sheet, which was recorded as a test sample; a lithium-sulfur battery positive electrode sheet without any catalyst was used as a blank test. Specifically, the positive electrode sheet was mixed with 70% sulfur and 30% carbon nanotubes by mass in a ball mill, and then kept warm at 155°C under semi-vacuum for 9 hours to obtain an active material for the electrode sheet, and then mixed with active material: binder = 9:1, and then coated, dried and cut to obtain a positive electrode sheet, which was recorded as a control sample.
[0176] (2) The positive electrodes of the test sample and the control sample lithium-sulfur battery were assembled into CR2025 button batteries with lithium sheets and PP separators, and 70uL 1M LiTFSIDOL / DME+2%LiNO 3
[0177] The assembled battery was subjected to a cyclic voltammetry test at 0.1 mV·s -1 The CV curve is obtained by scanning rate measurement. The results are as follows Figure 7 .according to Figure 7 It can be seen that after adding the catalyst of Example 1, the first and second reduction peaks of polysulfide in the CV curve are sharper and have larger peak values, and the pressure difference between the redox peaks is smaller, indicating that the catalyst has a significant catalytic conversion effect on the conversion of polysulfide, which is beneficial to improving the specific capacity of lithium-sulfur batteries, quickly converting polysulfides, inhibiting polysulfide shuttling, and thereby enhancing the battery cycle stability.
[0178] The inventors also carried out the above test on the catalysts of other embodiments, and the results were basically the same. Due to limited space, they are not listed one by one.
[0179] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A high entropy oxide catalyst, characterized in that: The general formula of the catalyst is (Cr a Co b Zn c M d N e )2O x , wherein 0.15≤a≤0.25, 0.15≤b≤0.25, 0.15≤c≤0.25, 0.15≤d≤0.25, 0.15≤e≤0.25, and a+b+c+d+e=1, 0.8≤x≤1.5, M and N are any one of Mn, Fe, and Cu respectively, and M and N are different elements.
2. A high entropy oxide catalyst according to claim 1, characterized in that: The high entropy oxide catalyst is a single-phase face-centered cubic high entropy oxide with uniform element distribution and a particle size of submicron level.
3. A method for preparing a high entropy oxide catalyst according to claim 1 or 2, characterized in that: The steps include: (1) weighing the metal powders according to the molar ratio, mixing to obtain a mixed metal powder, and ball milling to obtain a powder; (2) calcining the powder to obtain the high entropy oxide catalyst.
4. The method according to claim 3, characterized in that In step (1), an organic solvent is also added during the ball milling process. The mass of the organic solvent is 2-4% of the mass of the mixed metal powder. Preferably, the organic solvent is toluene and / or anhydrous ethanol.
5. The method according to claim 3, characterized in that: In step (1), the rotation speed of the ball mill is 250 to 350 rpm, and the ball milling time is 25 to 40 hours.
6. The method according to claim 5, characterized in that The ball milling was performed at least 60 times.
7. The method according to claim 6, characterized in that The single ball milling time is 30 to 40 minutes, and the interval between two adjacent ball millings is 3 to 5 minutes. After the ball milling is completed, the powder is naturally cooled in the tank for 12 to 36 hours.
8. The method according to any one of claims 3 to 7, characterized in that: In step (2), the calcination temperature is 400-600°C, the calcination time is 1-3h, and the heating rate is 5-10°C / min.
9. A sulfur positive electrode sheet for a lithium-sulfur battery, characterized in that: The invention comprises the high entropy oxide catalyst according to claim 1 or 2 or a high entropy oxide catalyst prepared by the method of any one of claims 3 to 8.
10. A lithium-sulfur battery, characterized in that: Including the positive electrode sheet as described in claim 9.